Towards advancements of a knowledge-based economy: Suggestions from the Gaza Phoenix strategic plan - Borri, Dino; Scandale, Luca (Plurimondi, 2025)
Knowledge-based economies appear to have strong relations with tradition and identities in social organizations. Complex settlements coming from varieties of language and stories and of special relations between human agents and space are knowledge-based fabrics for intensive knowledge-based economies. This paper explores the potential for Gaza's reconstruction through an endogenous development strategy rooted in regional science research, focusing on traditional sectors, youth engagement, symbolic places, and human capital development as pillars for building a resilient knowledge-intensive economy.